Dinâmica do CO2 em ecossistemas aquáticos na bacia Central Amazônica: uma abordagem em múltiplas escalas - Amaral, João Henrique Fernandes (Instituto Nacional de Pesquisas da Amazônia - INPA, 2017)
Amazon floodplains liberate large quantities of CO2 to the atmosphere, influencing both the regional and global carbon balance. The dynamics of CO2 on these floodplains varies spatially among aquatic habitats, seasonally in synchrony with the annual hydrological cycle, daily in response to diel stratification and metabolic cycles and between years in response to regional climate variation. We investigated variations in the concentration and surface emission of CO2 at multiple scales, including 1) seasonal variations in the open water habitats of river channels and lakes along the Solimões/Amazonas and Negro rivers during six fluvial expeditions between July of 2011 and December of 2012 and 2) daily, seasonal and interannual variations in three habitats at two meteorologically distinct sites on a central Amazon floodplain lake (Janauacá Lake; [3o23' S; 60o18' W]), using high resolution measurements at monthly intervals between August of 2014 and September of 2016. At the same times and locations of the gas measurements, we monitored limnological and meteorological variables that could influence CO2 dynamics. Using data from the fluvial expeditions and multiple linear models, we showed that the pCO2 levels in aquatic environments of the Negro and Solimões/Amazon rivers, biogeochemically distinct systems, were regulated by the same biophysical factors. Using data from Janauacá Lake, we demonstrated that physical and biological factors simultaneously influenced the concentrations and emissions of CO2. Variations in water level in these floodplains controlled the distribution and dynamics of aquatic primary producers and their influence on variations in the concentration and flux of CO2. Values of the gas transfer velocity (K) were lower in flooded macrophytes and forests than in open water environments, a result that has implications for regional emission estimates. Finally, from estimates of plankton community metabolism, we demonstrated that phytoplankton are capable of assimilating large quantities of dissolved CO2. Hence, a portion of the CO2 liberated during episodic events of macrophyte decomposition can be converted to organic carbon as phytoplankton biomass increases. The intensity and importance of planktonic metabolism to the carbon balance of these systems depends on the depth and wind exposure of open water environments.
Keywords: Dióxido de carbono; Planície de inundação; Sazonalidade; Metabolismo ecossistêmico Mudanças climaticas; Mudanças climáticas